Shaping a decolonised Sport History Curriculum through the national question (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
A renewed interest in decolonising the university curriculum in South Africa was sparked by the student protests of 2015. University faculties and departments throughout the country responded. Sport Science departments, the home of sport history modules, remained, however, aloof and removed from this development. This paper attempts to rupture this silence by addressing decolonisation of sport history at a conceptual curriculum level through the lenses of the National Question. After an introduction, a discussion of decolonisation and decoloniality is presented. This is followed by a conversation on sport history curriculum. Finally, I venture to suggest theoretical underpinnings for a decolonised sport history curriculum.
Keywords: Curriculum; Decolonisation; National Question; Sport history; Sport historian